Cellular mechanisms for heavy metal detoxification and tolerance - Hall, J L (Journal of experimental botany, 2002)
Heavy metals such as Cu and Zn are essential for normal plant growth, although elevated concentrations of both essential and non-essential metals can result in growth inhibition and toxicity symptoms. Plants possess a range of potential cellular mechanisms that may be involved in the detoxification of heavy metals and thus tolerance to metal stress. These include roles for the following: for mycorrhiza and for binding to cell wall and extracellular exudates; for reduced uptake or efflux pumping of metals at the plasma membrane; for chelation of metals in the cytosol by peptides such as phytochelatins; for the repair of stress-damaged proteins; and for the compartmentation of metals in the vacuole by tonoplast-located transporters. This review provides a broad overview of the evidence for an involvement of each mechanism in heavy metal detoxification and tolerance